1991
DOI: 10.1007/bf01980874
|View full text |Cite
|
Sign up to set email alerts
|

The intracerebroventricularly administered mast cells degranulator compound 48/80 increases the pituitary-adrenocortical activity in rats

Abstract: The effect of brain mast cells degranulation by compound 48/80 on the pituitary-adrenocortical activity, measured indirectly through corticosterone secretion, and the involvement of a histaminergic mechanism in that stimulation was investigated in conscious rats. All the drugs were given intracerebroventricularly (icv), histamine antagonists 15 min prior to compound 48/80. Compound 48/80 induced a significant dose- and time-related increase in the serum corticosterone levels. That increase, measured 1 h after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 28 publications
0
9
0
3
Order By: Relevance
“…To understand the underlying mechanism of this phenomenon, we examined the serum corticosterone level of rats exposed to CSD and treated with ranitidine or cimetidine which is significantly lower than that of the rats exposed to CSD and receiving placebo. Cerebral histamine is produced by mastocytes which can activate the HPA axis after stimulation [22]. It is possible that the H 2 receptor antagonists such as ranitidine and cimetidine may affect histamine to activate HPA axis through blocking the H 2 receptor in the brain, which decrease serum corticosterone level and suppress the depression-like behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the underlying mechanism of this phenomenon, we examined the serum corticosterone level of rats exposed to CSD and treated with ranitidine or cimetidine which is significantly lower than that of the rats exposed to CSD and receiving placebo. Cerebral histamine is produced by mastocytes which can activate the HPA axis after stimulation [22]. It is possible that the H 2 receptor antagonists such as ranitidine and cimetidine may affect histamine to activate HPA axis through blocking the H 2 receptor in the brain, which decrease serum corticosterone level and suppress the depression-like behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is confirmed by the fact that in our concurrent experiments the total degranulation of the rat brain mast cells by compound 48/80 administered intracerebroventricularly did not diminish the brain histamine levels. Also the histamine blockers mepyramine and cimetidine given into cere bral ventricles did not considerably change the corticosterone response induced by cen tral administration of compound 48/80 [25], Therefore, these findings indicate that the brain histamine involved in the opioid-in duced increase in corticosterone secretion is located mainly in the neuronal pool. In in vivo experiments on rats the most pro nounced histamine depletion (below 40% of the control value), observed in different brain structures, occurred 2-4 h after sys temic treatment with a-FMH [26,27].…”
Section: Discussionmentioning
confidence: 57%
“…It is known that histamine receptors are densely concentrated in the thalamus (Pillot et al, 2002) and can control presynaptic glutamate release (Garduno-Torres et al, 2007). Moreover, thalamic mast cell degranulation and histamine release coincides with corticosterone secretion (Bugajski et al, 1995), which is reduced by pretreatment with histamine receptor antagonists (Gadek-Michalska et al, 1991). Previously, it has been shown that mast cells can express corticotrophin-releasing factor receptors (Cao et al, 2005) and can even release corticotrophin-releasing factor (Theoharides et al, 2004) and corticosterone (Csaba et al, 1967).…”
Section: Discussionmentioning
confidence: 99%